Out of sorts : making peace with an evolving faith - Bessey, Sarah (Howard Books, 2015)
Bessey helps us grapple with core Christian issues by sharing her own wrestlings with core issues, such as who Jesus is, what place the Church has in our lives, how to disagree yet remain within a community. In doing so, she teaches us how to be as comfortable with uncertainty as we are with solid answers, in order to discover new depths of faith that will remain secure even through the storms of life.